Isolation, genetic characterization, and virulence profiling of different Aeromonas species recovered from moribund hybrid catfish (Clarias spp.) - Mulia, Dini Siswani; Pratiwi, Rarastoeti; Asmara, Widya; Sayuti, Mohamad Azzam; Md. Yasin, Ina Salwany; Isnansetyo, Alim (Veterinary World, 2023)
Background and Aim: The high diversity of Aeromonas spp. results in various pathogenicity levels. This group of bacteria causes a serious disease named motile Aeromonas septicemia (MAS) in catfish (Clarias spp.). This study aimed to characterize the species and virulence gene diversity of Aeromonas spp. isolated from diseased catfish. Materials and Methods: Nine Aeromonas spp. were isolated from infected catfish cultivated in Java, Indonesia, and they were identified at the phenotypic and molecular levels (16S rDNA). The virulence genes assessed included aer/haem, alt, ast, flaA, lafA, and fstA. Results: Phylogenetic analysis identified nine isolates of Aeromonas spp.: Aeromonas hydrophila (11.11%), Aeromonas caviae (11.11%), Aeromonas veronii bv. veronii (44.44%), and Aeromonas dhakensis (33.33%). Virulence genes, such as aer/haem, alt, ast, flaA, lafA, and fstA, were detected in all isolates at frequencies of approximately 100%, 66.67%, 88.89%, 100%, 55.56%, and 66.67%, respectively. This study is the first report on A. dhakensis recovered from an Indonesian catfish culture. Furthermore, our study revealed the presence of A. veronii bv veronii, a biovar that has not been reported before in Indonesia. Conclusion: This finding confirms that MAS was caused by multiple species of Aeromonas, notably A. dhakensis and A. veronii bv veronii, within Indonesian fish culture. The presence of these Aeromonas species with multiple virulence genes poses a significant threat to the freshwater aquaculture industry.